Learning Methods in the Perspective of the Qur'an and Hadith - Konita Lupiah; Andi Abd. Muis; Sugeng Sugiharto (Universitas Muhammadiyah Palu, 2025)
In the era of globalization, effective learning methods are crucial to improve the quality of education. The Quran and hadith as the main source of Islamic teachings offer various principles that can be adapted in learning methods. Social facts show that many educational institutions still use conventional methods that are less effective. According to data from the Ministry of Education and Culture of the Republic of Indonesia, around 60% of students feel less interested in existing learning methods (Ministry of Education and Culture, 2022). This indicates the need for innovation in teaching methods that can interest students and improve their understanding. In this context, the Quran and hadith teach the importance of comprehensive, interactive, and experiential learning. The research method used in this study is qualitative with a phenomenological approach. This research involves direct observation in several schools that apply Quran-based learning methods and hadith. In addition, interviews with teachers and students were also conducted to explore their experiences and views on the method. The collected data is then analyzed with thematic analysis techniques to identify emerging patterns and themes. The purpose of this research is to identify and analyze learning methods that are in accordance with the values contained in the Quran and hadith. In addition, this study also aims to provide recommendations for educators in implementing these methods in daily practice. Thus, it is hoped that a learning environment that is more conducive and in accordance with Islamic teachings can be created. The hypothesis of this study states that the application of learning methods based on the Qur'an and hadith can increase student motivation and learning outcomes. Previous research has shown that students who learn with an approach that integrates spiritual values tend to have better academic performance (Mulyadi, 2020). Therefore, this research is expected to make a significant contribution to the development of better education in Indonesia.